A Comparative Review of Autologous Conditioned Serum and Autologous Protein Solution for Treatment of Osteoarthritis in Horses - Camargo Garbin, Livia; Morris, Michael J. (Frontiers in Veterinary Science, 2021)
Many alternative treatments aimed at modulating osteoarthritis (OA) progression have been developed in the past decades, including the use of cytokine inhibitors (1). IL-1β is considered one of the most impactful cytokines in OA disease and therefore, its blockage offers a promising approach for the modulation of OA (2). Interleukin-1 receptor antagonist (IL-1Ra) is a naturally anti-inflammatory protein belonging to the IL-1 family that competes with IL-1β for occupancy of its receptors, without triggering the same downstream inflammatory response. Because of its natural anti-inflammatory properties, different methods have been proposed to use IL-1Ra therapeutically in OA. Autologous conditioned serum (ACS) and autologous protein solution (APS) are blood-derived products produced with the use of specialized commercial kits. These processes result in hemoderivatives with high concentrations of IL-1Ra and other cytokines and growth factors with potential modulatory effects on OA progression. Several studies have demonstrated potential anti-inflammatory effect of these therapies with promising clinical results. However, as with any hemoderivatives clinical outcomes may vary. For optimal therapeutic use, further research is warranted for a more comprehensive understanding of the product’s composition and interaction of its components in joint inflammatory processes. Additionally, differences between ACS and APS treatments may not be clear for many clients and clinicians. Thus, the objective of this narrative review is to guide the reader in important aspects of ACS and APS therapies, in vitro and in vivo applications and to compare the use of both treatments in OA.